Effect of epiphytic microflora after aerobic enrichment and reconstitution on fermentation quality and microbial community of corn stalk silage and Pennisetum sinese silage - Xie, Yixiao; Du, Ermei; Yao, Yudie; Wang, Wanqing; Huang, Xiaokang; Sun, Hong; Zheng, Yulong; Cheng, Qiming; Wang, Chunmei; Chen, Chao; Li, Ping (Frontiers in Microbiology, 2022)
The objective of this study was to evaluate the effects of enrichment and reconstitution of the forage epiphytic microflora on the fermentation quality, chemical composition, and bacterial community composition of corn stalk and Pennisetum sinese silages. The forage juice of fresh corn stalk and P. sinese were collected, diluted by gradient (10-1 to 10-5), and aerobically incubated to enrich and reconstitute the epiphytic microflora. Fresh corn stalk and P. sinese were ensiled for 3, 15, and 45 days after inoculation with either the original (D0) pre-incubated juices, or 10-1 (D1), 10-3 (D3), or 10-5 (D5) diluted and pre-incubated juices. The lowest pH was found in the D3 treatment of the corn stalk silage. In P. sinese silage, the hemicellulose content of D3 and D5 treatments was 9.50% and 11.81% lower than that of D0 treatment (P < 0.05). In corn stalk silage, the neutral detergent fiber content was significantly lower in the D3 treatment than in the other treatments (P < 0.05). Both corn stalk and P. sinese silages exhibited a high abundance of Enterobacter during ensiling, resulting in high levels of acetic acid. Although the dilution and enrichment of the epiphytic microflora did not lead to full lactic acid fermentation, these pre-treatments were found to alter the microbial metabolites and chemical composition of the silage. These results provide a new perspective on the production of pre-fermented silage inoculant.